Challenges and opportunities in early identification and intervention for children at-risk for autism spectrum disorders. (February 2014) - Crais, Elizabeth R.; Watson, Linda R.
Abstract This response to Camarata (2014) both agrees and disagrees with a number of points relative to early identification and intervention for children with autism spectrum disorders (ASD). The authors, too, recognize the difficulties of identifying toddlers with ASD and the complexities of intervening with these children. It is, however, suggested that there are alternatives to choosing to wait until diagnoses for at-risk children are stable and it is believed that there are many potential benefits from intervening, even when stable diagnoses cannot be made at the time, but risk markers are present. Specifically, it is suggested that it is not necessary to differentially diagnose children in efforts to evaluate treatment effects and suggestions are provided for alternative methods. This commentary also acknowledges the importance of effective ASD screening tools, along with expert clinical opinion, to help identify these toddlers with and at-risk for ASD. Both the available literature from other researchers as well as the authors' own work in these areas are used to make these arguments.